2004
DOI: 10.1017/s1047951104004081
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cardiac malformations in Iceland from 1990 through 1999

Abstract: The annual incidence of diagnosis of patients with congenital cardiac malformations increased during the period of study. This was noted for minor defects, but the incidence of the major anomalies did not alter. Our observed yearly incidence, at 1.7%, was higher than noted in a previous study covering the years 1985 through 1989, and is also higher than in other population-based studies. The most likely explanation is the fact that access to pediatric cardiologists in Iceland is very good. Diagnosis, registrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 16 publications
2
31
2
3
Order By: Relevance
“…3.1% of patients were diagnosed during prenatal period. In international literature, 43.6% of patients with heart disease are diagnosed during the first week of life, 70% are diagnosed up to six months old, and 86% are diagnosed up to two years old 10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3.1% of patients were diagnosed during prenatal period. In international literature, 43.6% of patients with heart disease are diagnosed during the first week of life, 70% are diagnosed up to six months old, and 86% are diagnosed up to two years old 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, these patients have been examined frequently, increasing estimated values. A prospective study in Iceland 10 showed a trend of increasing prevalence of mild heart diseases, probably due to great efficiency in diagnosis and abortion procedures in cases of more severe injuries. Incidence of severe heart diseases, in that study, had no changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…The rate for atrioventricular septal defect is 4.3%, mean 196 percentage with regards to reports from other registries with rates from 1.34% to 7.4% [6,33]. Incidence of 197 atrioventricular septal defects varies in accordance with the age of the involved mothers due to fact that the 198 Down syndrome is more common in mothers who are more than 34 years old, and atrioventricular septal defects 199 are very frequent in those with Down syndrome [5,13].…”
mentioning
confidence: 85%
“…The 229 proportion of comorbidity is between 4-45% depending on many factors [4,6,[9][10][11]20,24,27,28,33]. The 230 prevalence of congenital heart disease associated with chromosomal anomalies depends on the maternal age 231 profile in the country, the proportion of chromosomal cases diagnosed prenatally followed by termination of 232 pregnancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation